Assuring food and nutrition security in the time of AIDs - Gillespie, Stuart; Kisamba-Mugerwa, Wilberforce; Loevinsohn, Michael E. (International Food Policy Research Institute, 2004)
The interactions between HIV/AIDS and food and nutrition insecurity are becoming clearer as research fills knowledge gaps. To address these gaps, different actors (from individual household members to national policymakers) need tools and processes to turn growing knowledge into appropriate action. One such tool is the HIV/AIDS lens. Through such mainstreaming of HIV/AIDS into food- and nutrition-relevant policy, evidence of what works is progressively built up, learning is enhanced, and people are ultimately better equipped to address the multiple threats of the pandemic. -- from Text